Access to Education: Breaking Barriers with AI. (Diversity Research: Journal of Analysis and Trends, 2025)
Education has always been a cornerstone of personal and societal development. However, significant barriers such as geography, economic constraints, disabilities, and limitations in traditional infrastructure continue to prevent many individuals from accessing quality education. The rise of Artificial Intelligence (AI) is transforming this landscape by offering innovative solutions that make education more inclusive, personalized, and accessible. AI has the potential to revolutionize how people learn by personalizing content, overcoming language and accessibility obstacles, reducing costs, and scaling educational resources. This article explores how AI is reshaping education to become more equitable, especially for marginalized and underserved communities. Through remote learning, intelligent tutoring systems, and inclusive design, AI is paving the way for a more inclusive, equitable, and efficient global education system